Sustainable coastal management and climate adaptation : global lessons from regional approaches in Australia - Kenchington, R. A.; Stocker, Laura J., 1961-; Wood, David (Collingwood, VIC : CSIRO Pub., 2012)
Explores evolution of coastal management, provides critical insights into contemporary experience, understanding of coastal management in Australia. Draws on contemporary theory, lessons from case examples to highlight roles of research, community engagement in coastal management. Wood and Stocker at Curtin University.
Includes bibliographical references and index.
Keywords: Coastal ecology -- Environmental aspects -- Australia; Climatic changes -- Environmental aspects -- Australia; Ecology -- Research -- Australia; Coastal zone management -- Australia; Meteorology & climatology; Conservation of the environment